Analyzing body dissatisfaction and gender dysphoria in the context of minority stress among transgender adolescents - Alexandra Brecht; Sascha Bos; Laura Ries; Kerstin Hübner; Pia-Marie Widenka; Sibylle Maria Winter; Claudia Calvano (BMC, 2024)
Abstract Background Gender dysphoria among transgender adolescents has predominantly been examined in relation to body dissatisfaction. While in adult transgender samples, body dissatisfaction is higher than in cisgender controls, this has so far rarely been investigated for adolescents. In the context of a cisnormative society, the impact of influences from the social environment on body dissatisfaction and gender dysphoria has been neglected in research. Therefore, this study aimed to (1) provide a detailed analysis of body dissatisfaction among young transgender people and (2) investigate whether body dissatisfaction and gender dysphoria are associated with experiences of minority stress such as trans hostility and poor peer relations (PPR). Methods The paper presents a cross-sectional study among a sample of transgender adolescents, presenting at a specialized outpatient counseling clinic (N = 99; age M = 15.36, SD = 1.85). First, body dissatisfaction (assessed by the Body-Image-Scale; BIS), was explored and compared to data from a population-based control group of cisgender peers (N = 527; age M = 14.43, SD = 0.97). Second, within a clinic-referred transgender subsample (n = 74), associations between body dissatisfaction and gender dysphoria (measured by Utrecht Gender Dysphoria Scale; UGDS), PPR (measured by the Youth-Self-Report; YSR-R), and trans hostile experiences (assessed in clinical interview) were examined by correlations, t-tests and multivariate regression. Results Transgender adolescents reported more body dissatisfaction than cisgender peers. The dissatisfaction with sex characteristics, non-hormonal reactive body regions and the total score for body dissatisfaction were positively related with gender dysphoria. The majority had experienced trans hostility in the present and/or past (54.1%) and PPR (63.5%). More body dissatisfaction was correlated with more PPR regarding visible body parts i.e., hair, overall appearance and muscles, whilst PPR and gender dysphoria were not associated. Transgender adolescents who experienced trans hostility showed higher gender dysphoria and PPR, but not more body dissatisfaction. In multiple regression, trans hostility predicted gender dysphoria, whilst age and PPR predicted body dissatisfaction. Discussion Experiences of minority-stress differentially interact with body dissatisfaction and gender dysphoria among transgender adolescents. Social correlates of body dissatisfaction and gender dysphoria must be considered when working with young transgender people.